The origin of Cihara granodiorite from South Banten - Hartono, Udi; Syafri, Ildrem; Ardiansyah, Reza (Indonesian Journal on Geoscience, 2008)
http://dx.doi.org/10.17014/ijog.vol3no2.20085Petrographical and geochemical characteristics of the Late Oligocene Cihara Granodiorite from South Banten are presented. Data show that the rock was originated from magma of a continental origin formed at a subduction zone environment. Fractional crystallization involving plagioclase, hornblende, pyroxene, and magnetite was the main process responsible for the geochemical variation of the rocks from the Cihara Granodiorite. There are two possibilities of parental magmas to the Cihara Granodiorite, i.e. the basaltic/ or andesitic magma of the Cikotok Formation or crustal melting magma from a subduction process. Some trace element data of the basaltic rocks from the Cikotok Formation are needed to support the first interpretation. Alternatively, heating of the Jawa lower crust by magma from either mantle or subducted slab melting caused the crustal melting to produce intermediate parent magma. Some degree of mixing between those two differ- ent magma sources during the fractionation may be involved in the petrogenesis. Â  Â